Lisbon - Tranaeus, Tomas (DK eyewitness top 10 travel guides., 2015)
Provides travel information on Lisbon, Portugal; recommends the 10 best restaurants, bars, hotels, entertainment, and outdoor activities, along with information on trip planning, nightlife, and shopping.